Endothelial cell-by-cell profiling reveals the temporal dynamics of VEGFR1 and VEGFR2 membrane localization after murine hindlimb ischemia - Imoukhuede, P. I. (American Physiological Society, 2013)
VEGF receptor (VEGFR) cell surface localization plays a critical role in transducing VEGF signaling toward angiogenic outcomes, and quantitative characterization of these parameters is critical to advancing computational models for predictive medicine. However, studies to this point have largely examined intact muscle; thus, essential data on the cellular localization of the receptors within the tissue are currently unknown. Therefore, our aims were to quantitatively analyze VEGFR localization on endothelial cells (ECs) from mouse hindlimb skeletal muscles after the induction of hindlimb ischemia, an established model for human peripheral artery disease. Flow cytometry was used to measure and compare the ex vivo surface localization of VEGFR1 and VEGFR2 on CD31(+)/CD34(+) ECs 3 and 10 days after unilateral ligation of the femoral artery. We determined that 3 days after hindlimb ischemia, VEGFR2 surface levels were decreased by 80% compared with ECs from the nonischemic limb; 10 days after ischemia, we observed a twofold increase in surface levels of the modulatory receptor, VEGFR1, along with increased proliferating cell nuclear antigen, urokinase plasminogen activator, and urokinase plasminogen activator receptor mRNA expression compared with the nonischemic limb. The significant upregulation of VEGFR1 surface levels indicates that VEGFR1 indeed plays a critical role in the ischemia-induced perfusion recovery process, a process that includes both angiogenesis and arteriogenesis. The quantification of these dissimilarities, for the first time ex vivo, provides insights into the balance of modulatory (VEGFR1) and proangiogenic (VEGFR2) receptors in ischemia and lays the foundation for systems biology approaches toward therapeutic angiogenesis.